User acceptance of SaaS ERP considering perceived risk, system performance and cost - Lim, Tong Ming *; Lee, Angela Siew Hoong *; Yap, Mun Keong * (2016)
The use of cloud solution to support ERP system has become the priority of many organizations to stay competitive in the current global world. This research will be focusing on the user acceptance of SaaS ERP (SAP ByDesign) in a global construction tool provider considering perceived risk, cost and system performance. Due to many unique variables, the purpose of this research is to analyze and investigate issues related to acceptance of SaaS in the construction tool provider companies. The results of this research can help both organizations and researchers to build a fundamental level on understanding how these factors that can predict the user acceptance of SaaS ERP in a global construction tool provider company which significantly beneficial. 80 users ranging from executive and higher management level globally were targeted. SAS Enterprise Guide 5.1 was used to analyze respondents' data and SAS dataset was then run by SAS Enterprise Guide 5.1 to produce descriptive analysis, Cronbach alpha, factor analysis and PLS-SEM will be used to analyses the responses and each hypothesis will be tested based on the data consolidated. Lastly, Partial Least Square- SEM will be performed to summarize and give an analysis of the research model proposed